New species, new records and checklist of cicadas from Mexico (Hemiptera: Cicadomorpha: Cicadidae) - Sanborn, Allen F. (Zootaxa, 2007)
Seven new species and new records for 14 species and one subspecies of cicadas from Mexico are reported. New members of the Nearctic genera Odopoea Stål, O. minuta sp.n., Chinaria Davis, C. pueblaensis sp.n., Diceroprocta Stål, D. oaxacaensis sp.n. and D. pronotolinea sp.n., Tibicen Latrielle, T. chihuahuaensis sp.n., Procollina Metcalf, P. queretaroensis sp.n., and Herrera Distant, H. coyamensis sp.n., are described. The first records of Diceroprocta cinctifera viridicosta Davis, Diceroprocta swalei (Distant), Tibicen chiricahua Davis, Tibicen chisosensis Davis, Tibicen cultriformis (Davis), Cornuplura nigroalbata (Davis), Cacama californica Davis, Cacama variegata Davis, Platypedia aperta Van Duzee, Platypedia minor Uhler, Okanagana triangulata Davis, Okanagana vanduzeei Distant, Clidophleps distanti (Van Duzee), Clidophleps distanti truncata (Van Duzee), and Clidophleps wrighti Davis from Mexico are also reported. Fidicina compostela Davis, 1934 is transferred to Fidicinoides Boulard & Martinelli. This work increases the Mexican cicada diversity by 18.8% bringing the total diversity to 117 taxa, 46.2% of which are endemic. The Mexican fauna is composed of both tropical and temperate genera with the generic diversity heavily influenced by the expansion of tropical genera into southern Mexico.